2015
DOI: 10.3109/02713683.2015.1037926
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Anti-angiogenic and Anti-inflammatory Effects of Two Antibiotics: Clarithromycin Versus Moxifloxacin

Abstract: Clarithromycin suppressed LY and inflammation in the cornea, and its anti-inflammatory effect was significantly superior to that of moxifloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Moxifloxacin is a fourth-generation QN that has a strong antibacterial activity in Gram-positive and Gram-negative bacteria, and thus has wide clinical uses. In recent years, a number of studies have demonstrated the immunomodulatory effects of MXF ( 49 52 ). Anti-infection therapies should not only consider the sensitivity and potency of antibacterial agents; however, the association between antibacterial in vivo efficacy and immunoregulation additionally requires consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Moxifloxacin is a fourth-generation QN that has a strong antibacterial activity in Gram-positive and Gram-negative bacteria, and thus has wide clinical uses. In recent years, a number of studies have demonstrated the immunomodulatory effects of MXF ( 49 52 ). Anti-infection therapies should not only consider the sensitivity and potency of antibacterial agents; however, the association between antibacterial in vivo efficacy and immunoregulation additionally requires consideration.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been documented that AZM can inhibit epithelial-to-mesenchymal transition (EMT) in lung epithelium (Banerjee et al, 2012;Pu et al, 2018), further supporting its role as an epithelial barrier-protecting drug. Macrolides are also able to inhibit the release by fibroblasts of vascular endothelial growth factor, and this may contribute to inhibitory effects of clarithromycin on angiogenesis during chronic inflammation (Yatsunami and Hayashi, 2001;Kanoh and Rubin, 2010;Uehara et al, 2016).…”
Section: A Anti-inflammatory/immunomodulatory Effectsmentioning
confidence: 99%
“…Conservative therapeutic approaches aim to control causative factors, to alleviate pain and to restore a stable ocular surface in the early stage of LSCD, including nonpreserved lubricating eye drops, autologous serum drops, bandage contact lenses, anti-inflammatory drugs, and anti-angiogenic therapy [ 173 , 174 , 175 , 176 , 177 ]. Autologous serum eye drops as a natural preservative-free and growth factor-containing lubricant can promote corneal epithelial healing and medically reverse advanced LSCD [ 178 , 179 ].…”
Section: Therapy Of Lscdmentioning
confidence: 99%